Impact of seasonal biometeorological conditions and particulate matter on asthma and COPD hospital admissions - Anna Romaszko-Wojtowicz; Ewa Dragańska; Anna Doboszyńska; Katarzyna Glińska-Lewczuk (Scientific Reports)
Abstract Climate change and air pollution are pressing public health concerns, necessitating monitoring of their impact, particularly on respiratory diseases like obstructive lung diseases. This retrospective study analyzed medical records of patients hospitalized at the Warmia and Mazury Centre for Pulmonary Diseases in Olsztyn, Poland (2012–2021) for asthma and chronic obstructive pulmonary disease (COPD) exacerbations. Data included meteorological factors such as temperature, humidity, wind speed, precipitation, and levels of PM2.5 and PM10. The Humidex was utilized to assess thermal discomfort, considering various meteorological and thermal seasons. Findings indicated seasonal variability in asthma and COPD exacerbations. During winter, poorer air quality due to higher PM2.5 and PM10 levels correlated with increased exacerbations (r = 0.283, p < 0.05; r = 0.491, p < 0.001). In summer, discomfort from meteorological conditions led to more hospital admissions. Humidex values strongly correlated with admissions for obstructive diseases (R2 = 0.956 for asthma; R2 = 0.659 for COPD), with July and August showing statistically higher admission rates (p < 0.05). The study highlights the significant impact of air pollution and meteorological conditions on exacerbations of asthma and COPD, with Humidex serving as a valuable predictor during summer months.